2020
DOI: 10.3390/brainsci10090590
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Thrombectomies in the Same Patient within One Month: Case Report of a Patient with Trousseau Syndrome and Acute Ischemic Stroke

Abstract: Background and Importance: Since Trousseau’s initial publication, the development of thromboembolic events related to malignancy has been well established. The pathophysiology of this is understood to be through activation of the coagulation cascade through neoplastic cells themselves or the therapy initiated (chemotherapy or surgery). To date, there have been a variety of studies, such as the OASIS-CANCER trial, which highlight the relationship of hypercoagulability to ischemic stroke. Despite these efforts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…13,14) In these studies, risk factors of re-occlusion included the number of device passes, missed residual thrombus or stenosis on the past angiography after thrombectomy, intracranial ICA or M2 occlusion, stroke of undetermined cause, and statin pretreatment. 13,14) According to our research, there are 14 reported incidences of TS treated by MT with available literature [2][3][4]13,[15][16][17][18][19][20][21][22] (Table 1). Of half of the cases that experienced re-occlusion of the cerebral large vessels, five cases involved the same vessels.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…13,14) In these studies, risk factors of re-occlusion included the number of device passes, missed residual thrombus or stenosis on the past angiography after thrombectomy, intracranial ICA or M2 occlusion, stroke of undetermined cause, and statin pretreatment. 13,14) According to our research, there are 14 reported incidences of TS treated by MT with available literature [2][3][4]13,[15][16][17][18][19][20][21][22] (Table 1). Of half of the cases that experienced re-occlusion of the cerebral large vessels, five cases involved the same vessels.…”
Section: Discussionmentioning
confidence: 98%
“… 22) Cicilioni et al proposed the presence of circulating extracellular vesicles, which is associated with the activation of neutrophil extracellular traps and thrombus formation in the presence of an underlying malignancy. 19) Only two of these five cases described required retreatment. One case underwent contact aspiration (CA) again, while the other was performed stenting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a possibility of large vessel reocclusion relatively early after thrombectomy due to cancer-related stroke. [30][31][32] Large vessel reocclusion may contribute to poor outcome after thrombectomy due to cancer-related stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that LMWH is the preferred treatment and prevention method for cancer-related thromboembolic events, and oral anticoagulant drugs have been shown to be ineffective. [4] In the OASIS-CANCER trial, suggested that successful correction of hypercoagulability based on D-dimer values was associated with improved survival and reduced recurrence. [5] This relies mainly on LMWH.…”
Section: Discussionmentioning
confidence: 99%